Resting-state functional connectivity of anterior and posterior hippocampus in posttraumatic stress disorder. (November 2017) - Lazarov, Amit; Zhu, Xi; Suarez-Jimenez, Benjamin; Rutherford, Bret R.; Neria, Yuval
Abstract: Posttraumatic stress disorder (PTSD) has been associated with altered resting-state functional connectivity (rs-FC) of several brain regions within the salience (SN) and default-mode (DMN) networks, including the hippocampus. However, most rs-FC studies have not focused primarily on the hippocampus, nor have they appreciated its structural heterogeneity, despite clear evidence for a dissociation between posterior and anterior hippocampal connectivity. Here, we examine rs-FC of anterior and posterior hippocampus with key regions in the SN (amygdala, insula, and dorsal anterior cingulate cortex/pre-supplementary motor area) and DMN (ventromedial prefrontal cortex, posterior cingulate cortex, and precuneus) previously implicated in PTSD, using a seed-based approach. Resting-state magnetic resonance images were obtained from 48 PTSD patients and 34 trauma-exposed healthy participants (TEHC). Results indicated no group differences when examining the hippocampus as a whole. However, examining the anterior and posterior hippocampus revealed a loss of anterior to posterior connectivity differentiation in PTSD patients. The PTSD group also demonstrated lower negative connectivity of the posterior hippocampus-precuneus pathway compared with the TEHC group. Finally, as differences in anterior and posterior hippocampus connectivity have been also related to age, we performed a secondary analysis exploring the association between age and posterior- and anterior-hippocampus connectivity in both groups. Results showed that among PTSD patients, increased age had the effect of normalizing posterior hippocampus-precuneus and hippocampus-posterior cingulate cortex connectivity, whereas no such effect was noted for the control group. These findings highlight the need for PTSD connectivity research to consider sub-parts of the hippocampus and to account for age-related connectivity differences. Highlights: PTSD is characterized by lack of anterior-posterior connectivity differentiation. PTSD is associated with lower negative posterior hippocampus-precuneus connectivity. No findings emerge when examining the hippocampus as a whole. In PTSD age is associated with normalized posterior hippocampus connectivity.